Red Dirt Thinking on first language and culturally responsive pedagogies in Anangu schools. Issue 3 (1st September 2020) - Osborne, Sam; Lester, Karina; Tjitayi, Katrina; Burton, Rueben; Minutjukur, Makinti
ABSTRACT: Recent research relating specifically to Anangu (Pitjantjatjara and Yankunytjatjara) schools in South Australia and the Northern Territory assert that Aboriginal people living in remote central Australian communities viewed first languages and cultures as central to a good education for their children. The South Australian ten-year Aboriginal Education Strategy (2019–2029) commits to culturally responsive pedagogies (CRP) and bilingual instruction in Anangu schools by 2029. This translation from research to policy has important implications for practice which the authors, five experienced practitioner-researchers in Anangu education contexts, reflect on through a "practice architectures" lens using a narrative methodology. The article explores the complex space that practitioner researchers negotiate and highlights the shifts required in moving from research-oriented arguments to working collaboratively to enacting research findings in practice. The article concludes with reflections on privileging community voices and demands throughout the research-policy-practice continuum.